Development of Rating Curve for River Ngadda - Ibrahim, U. A.; Daniel, P.; Gutti, M. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Accurate river discharge estimation is critical for sustainable water resource management and infrastructure design, especially in areas where data scarcity is a major concern. This study addresses this issue by developing a rating curve for the Ngadda River in Borno State, Nigeria. The lack of continuous discharge data and reliable rating curves has historically hindered water resource project planning in the region. Leveraging stage-discharge rating curves and utilizing an optimization-based technique with Excel solver, curve parameters were calibrated to accurately depict the hydraulic relationship between river stage and discharge. The analysis of discharge data at Logojeri and Maiduguri gauging stations revealed seasonal changes in river flow, emphasizing the importance of continuous monitoring for effective water resource management. Correlation analysis between actual and predicted discharge confirmed the reliability of the developed rating curve, while uncertainty analysis revealed insights into potential errors associated with the discharge estimation. The developed rating curve which is for the two specific gauging stations (Maiduguri and Logojeri), provides a useful tool for converting stage data into discharge values, thereby assisting with water resource planning and decision-making. It is therefore urged for ongoing monitoring efforts and the installation of monitoring tools to modify and improve the developed rating curve's ability to capture the dynamic hydrological behavior of the Ngadda River.